On the question of detecting granulation signal in CoRoT light curves of A and B stars - Ghazaryan, S. (Advances in Astronomy and Space Physics, 2013)
We applied the procedure written by us to HgMn targets observed both through CoRoT astero and exo channels to check its usefulness for search of possible existence of solar-type granulation signature in their power spectrum. The point is that many articles appeared very recently considering this problem but, we did not find any paper on this issue in relation to chemically peculiar main-sequence stars. Because theoretical models based on atomic diffusion require that the atmospheres of ApBp stars have to be more stable than those of normal stars, presence or absence of granulation on their surfaces should be an interesting information for modelling. The earliest results show that our method is appropriate for analysis of data obtained through astero and exo channels. Nowadays, solar-type granulation effect most likely has not be seen within CoRoT data for the stars we considered. This issue needs further consideration.